Draft Eleventh Five Year Plan 2007-12 and Annual Plan 2007-08 Orissa Volume-I - Planning Commission (Planning Commission, 2007)
Orissa is located on the eastern coast, surrounded by Andhra Pradesh, Chhattisgarh, Jharkhand and West Bengal. It has more than 480 km long coastline. It is the 8th largest State with an area of 1,55,707 km2. stands 11th largest in terms of population (36.80 million as per 2001 census), and is 14th with regard to population density (236 persons per km2 in 2001). Despite its rich natural resource endowment, Orissa continues to be very poor. It is regarded as the poorest major State.
Government of Orissa, Planning and Coordination Department
Government of Orissa, Planning and Coordination Department